Text and Understanding of Hadiths on Husband Wife Ethics: A Study of the Book of Jami' al-Tirmizi - Pengabdi Daulay; Ziaulhaq Hidayat; Sulaiman Muhammad Amir (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
Rising domestic conflict, divorce rates, and domestic violence suggest that Islamic ethical values regarding husband-wife relations remain poorly understood and implemented in society. Academic studies that comprehensively inventory and thematically analyze husband-wife ethics within a single Hadith collection remain limited; prior research tends to address family themes partially and rarely engages with contemporary gender discourse. This study addresses that gap by examining the text and meaning of Hadith on husband-wife ethics in Jami' al-Tirmidhi, situating the findings within contemporary gender debates. The study employs a qualitative method with a library-based approach. Primary data consist of Hadith on husband-wife ethics from Jami' al-Tirmidhi, while secondary data are drawn from syarah (commentary) texts, books, and journal articles. Data were collected through takhrij, documentation, and classification, followed by analysis of sanad, matan, and syarah, validated through source triangulation. Findings show that 15 Hadith can be grouped into five themes: morality toward one's spouse, responsibility for providing and leadership, wives' rights and obligations toward husbands, safeguarding honor, and balancing rights and obligations. These Hadith affirm that the husband-wife relationship in Islam is not hierarchical but a partnership grounded in complementary rights and obligations, open to dialogue with contemporary family and gender discourse.